One-year rehospitalisations for congestive heart failure in Portuguese NHS hospitals - Moita, Bruno (2019)
Objectives Identification of rehospitalisations for heart failure and contributing factors flags health policy intervention opportunities designed to deliver care at a most effective and efficient level. Recognising that heart failure is a condition for which timely and appropriate outpatient care can potentially prevent the use of inpatient services, we aimed to determine to what extent comorbidities and material deprivation were predictive of 1 year heart failure specific rehospitalisation. Setting All Portuguese mainland National Health Service (NHS) hospitals. Participants A total of 68 565 hospitalisations for heart failure principal cause of admission, from 2011 to 2015, associated to 45 882 distinct patients aged 18 years old or over. Outcome measures We defined 1 year specific heart failure rehospitalisation and time to rehospitalisation as outcome measures. Results Heart failure principal diagnosis admissions accounted for 1.6% of total hospital NHS budget, and over 40% of this burden is associated to patients rehospitalised at least once in the 365-day follow-up period. 22.1% of the patients hospitalised for a principal diagnosis of heart failure were rehospitalised for the same cause at least once within 365 days after previous discharge. Nearly 55% of rehospitalised patients were readmitted within 3 months. Results suggest a mediation effect between material deprivation and the chance of 1 year rehospitalisation through the effect that material deprivation has on the prevalence of comorbidities. Heart failure combined with chronic kidney disease or chronic obstructive pulmonary disease increases by 2.8 and 2.2 times, respectively, the chance of the patient becoming a frequent user of inpatient services for heart failure principal cause of admission. Conclusions One-fifth of patients admitted for heart failure are rehospitalised due to heart failure exacerbation. While the role of material deprivation remained unclear, comorbidities considered increased the chance of 1 year heart failure specific rehospitalisation, in particular, chronic kidney disease and chronic obstructive pulmonary disease.